Evaluation Gap of Internet Banking Service Quality by Using Servqual Approach - an Empirical Study of Indian Banks - Daneshvar, Poolad; Ramesh, H.N. (Journal of Information and Knowledge, 2010)
This paper deals with the concept of service quality and has demonstrated the model of service quality gaps; it aims to measure customers‟ gap between satisfaction levels of interpretation of services and their preferences of the interpretive service in internet banking at Indian commercial banks. The research questions are utilized to measure the gap between expectation and satisfaction levels of customers about quality of internet banking. For this purpose a questionnaire with five-point Likert scale is applied to measure customers expectation as well as satisfaction. Data was obtained from 102 respondents and analyzed using SPSS 12 software by employing factor analysis and multiple regressions. Results indicate that there are significant differences between overall expectations and satisfaction levels of customers. For practitioners, it is worth noting that customers are exclusively concerned with the "Sufficient menu for transaction"," Variety of services readily accessible", "Availability for business" and "Have a user-friendly system", as important factors for them to apply internet banking. The paper contains material relevant to the internet banking industry, and Implications are discussed and recommendations are offered for improving Internet banking services.